Motor skills of U15 category soccer players playing in different positions on the field - Wilk Adrian; Górski Michał; Pastuszak Anna; Michalak Bartłomiej; Rdzanek Justyna; Buśko Krzysztof (Biomedical Human Kinetics, 2025)
Study aim: The aim of the study was to evaluate the differences in strength and jumping abilities of adolescent soccer players playing in different positions on the field.